2013
DOI: 10.5897/ajps10.068
|View full text |Cite
|
Sign up to set email alerts
|

Study on malting barley genotypes under diverse Agroecologies of north western Ethiopia

Abstract: The study was conducted with the objectives to determine the magnitude effect of genotype, environment, and their interactions on economically important traits and identify stable malt barley (Hordeum distichon L.) genotypes. Combined analysis of variance indicated that the main effects due to environment, genotype and GxE interaction were highly significant for grain yield and economically important malting quality triats indicated that development of both specific and wide adaptable varieties are essential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…The first interaction principal component (IPCA 1) captured 29% of the variation and with the model fitness of 77% but the malt barley genotypes was more explained by the AMMI 2 biplot model analysis provided a model fitness of 89.36% and the result of the study was in agreement with Bantayehu (2013) that had found best model fitness using the second model AMMI 2. (Purchase, 1997) pointed out that the closer the genotypes score to the center of the biplot the more stable is the genotype and the reverse is true.…”
Section: Ammi 1 Biplotsupporting
confidence: 80%
“…The first interaction principal component (IPCA 1) captured 29% of the variation and with the model fitness of 77% but the malt barley genotypes was more explained by the AMMI 2 biplot model analysis provided a model fitness of 89.36% and the result of the study was in agreement with Bantayehu (2013) that had found best model fitness using the second model AMMI 2. (Purchase, 1997) pointed out that the closer the genotypes score to the center of the biplot the more stable is the genotype and the reverse is true.…”
Section: Ammi 1 Biplotsupporting
confidence: 80%
“…Combined application NPS fertilizer showed yields and yield component are significantly increased according to the repot of [28]. Similarly, the combined application of NPS fertilizer significantly increased spike length, Number of grains spike -1 , 1000-grain weight and grain yield by the crop [9,31,50,51,66].…”
Section: Effects Of Nps On Yield and Yield Component Of Food Barleymentioning
confidence: 99%
“…According to the Ethiopian quality standard, the acceptable grain size (thousand-kernel weight) and test weight (hectoliter weight) for raw barley are in the range 25-35 g and 48-62 kg hl -1 , respectively [47]. The standards set Response to Seeding Rate at Sinana District, Southeast Ethiopia for thousand kernel weight and hectoliter weight by National Standard Authority ranged from 35-45 g and 60-65 kg hl -1 , respectively [49]. Therefore, the results of the present experiment exhibited an acceptable thousand kernel and hectoliter weight in all varieties except HB-1964 variety and with the combination of 100 -150 kg ha -1 seed rate.…”
Section: Hectoliter Weightmentioning
confidence: 99%